2020
DOI: 10.1101/2020.01.24.918532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential combinations of chemotherapeutic agents with BH3 mimetics to treat rhabdomyosarcoma and avoid resistance

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in childhood and adolescence. Refractory/relapsed RMS patients present a bad prognosis that combined with the lack of specific biomarkers difficult the development of new therapies. We here utilize dynamic BH3 Profiling (DBP), a functional predictive biomarker that measures net changes in mitochondrial apoptotic signaling, to identify anti-apoptotic adaptations upon treatment. We use this information to guide the use of BH3 mimetics to specifically … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…S1i). In SKBR-3 cells, which express the highest cellular levels of FASN (up to 28% by weight of the cytosolic proteins) yet described in human established cell lines [26,27,51,52], a clear apoptotic synergism was observed when C75 was added to navitoclax/ABT-263, which had no impact against SKBR-3 cells as single agent (Fig. 4b).…”
Section: Fasn Inhibition Enhances Sensitivity To the Bcl-2 Family Inhibitor Navitoclax/abt-263mentioning
confidence: 96%
“…S1i). In SKBR-3 cells, which express the highest cellular levels of FASN (up to 28% by weight of the cytosolic proteins) yet described in human established cell lines [26,27,51,52], a clear apoptotic synergism was observed when C75 was added to navitoclax/ABT-263, which had no impact against SKBR-3 cells as single agent (Fig. 4b).…”
Section: Fasn Inhibition Enhances Sensitivity To the Bcl-2 Family Inhibitor Navitoclax/abt-263mentioning
confidence: 96%
“…Interestingly, this study showed that the observed acquired antiapoptotic dependence to the BRAF inhibitor dabrafenib was not mediated by an increase in MCL1 expression, but through a NOXA mRNA destabilization leading to protein decrease (151). Other novel therapeutic combinations with BH3 mimetics were recently identified using this approach in NSCLC (200), breast cancer (123,158,201,202), esophageal cancer/ mesothelioma (203), and pediatric cancers (146,204), among others. Depicting the complexity of these prosurvival adaptations and antiapoptotic cross-talk is key to accurately identifying the right drug combination and the optimal sequential administration to maximize the cytotoxic effect in tumors.…”
Section: Dynamic Biomarkers For Bh3 Mimeticsmentioning
confidence: 87%
“…Apart from the previously cited examples of BH3 mimetic combinations in hematologic malignancies, multiple reports demonstrated that BCL2/BCLXL inhibition combined with conventional chemotherapy was effective against many solid tumors, including breast cancer, ovarian cancer, neuroblastoma, NSCLC, and many others (32,44,130,(139)(140)(141)(142)(143)(144). Also, as new compounds emerge, MCL1 inhibition has been successfully used in preclinical studies to boost standard-of-care treatments in hepatocellular carcinoma (68), breast cancer (145), ovarian cancer (130), and rhabdomyosarcoma (146), among others.…”
Section: Reviewmentioning
confidence: 99%
“…To evaluate the ability of GNR-PEG-Ang2/D1 to cross the BBB, it was functionalized with the fluorophore Alexa647 and injected into the endothelial channel of the BBB-oC and fluorescent images were taken. Since Ang2 can penetrate the BBB by receptor-mediated endocytosis due to high LRP1 binding affinity, the expression of LRP1 in EC was confirmed by western blot [63] (Supplementary Figure S4) [65]. To evaluate the role of Ang2 in the entrance, nanoparticles without the shuttling peptide (GNR-PEG-D1) were used as control.…”
Section: Gnr-peg-ang2/d1 Permeability Performancementioning
confidence: 99%
“…Since Ang2 can penetrate the BBB by receptor-mediated endocytosis due to high LRP1 binding affinity, the expression of LRP1 in EC was confirmed by western blot [63] (Supplementary Figure S4) [65]. To evaluate the role of Ang2 in the entrance, nanoparticles without the shuttling peptide (GNR-PEG-D1)…”
Section: Gnr-peg-ang2/d1 Permeability Performancementioning
confidence: 99%